KAJIAN TEKNIS DESAIN DAN MANAJEMEN PENIMBUNAN BATUBARA DI ROM STOCKPILE PT. BARA MEGA QUANTUM KOTA BENGKULU PROVINSI BENGKULU: Technical Study And Management Design Of Coal Stock At Rom Stockpile PT. BaraMega Quantum, Bengkulu Central Regency, Bengkulu Province - M Dandy Al Fansya; Agus Winarno; Henny Magdalena; Windhu Nugroho; Sakdillah (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2022)
Stockpile is a temporary storage place for coal before it is sold to consumers. The stockpile must be properly regulated so that the quality of the coal is maintained, so that when it reaches the consumer it is still of the desired quality. The plan is that in November the coal that will be included in the ROM stockpile of PT. Bara Mega Quantum will experience changes, both in quality and quantity. This study aims to determine the readiness of the stockpile to face the planned increase in coal production. PT. Bara Mega Quantum has a ROM Stockpile which is located southwest of the mining site, precisely located in the coal processing area on Pulau Baai Terminal Coal PT. Pelindo Bengkulu, Kampung Melayu District, Bengkulu City, Bengkulu Province. Where the distance between the pit and ROM Stockpile is approximately 67 km. The processing area consists of ROM Stockpile, Hopper, and Jetty Loading. Based on calculations from rainfall data, the total water discharge entering the ROM Stockpile area is 4393,67 m3/day. To accommodate this amount water, sufficient dimensions of the settling pond are needed to prevent overflow. Based on the data processing carried out, the dimensions available sludge settling pond are 5960 m3. The height of the coal pile is taken based on the specifications of the Whell Loader with the Komatsu 350 type. The following is a picture of the dimensions of the Whell Loader with the Komatsu 350 type used in the ROM Stockpile activity by PT BMQ. In accordance with the design that has been made and the data that has been processed for the capacity of the coal stockpile on the ROM Stockpile, namely on ROM 1, ROM 2 and ROM 3, the volume obtained is 20214.58 m3 and for tonnage 26278,95 MT.